Spontaneous intracranial hypotension. Issue 5 (November 1995) - Renowden, S A; Gregory, R; Hyman, N; Hilton-Jones, D
Abstract : The clinical features and radiological appearances of spontaneous intracranial hypotension are described in three patients and the medical literature is reviewed. Awareness of this condition and its differentiation from more sinister meningitic processes is important to avoid unnecessary invasive investigations and to allow prompt diagnosis and effective treatment.